Physical exercise as treatment for adults with type 2 diabetes: a rapid review - Ribeiro, Andressa Karoline Pinto de Lima; Carvalho, Josilayne Patrícia Ramos; Bento-Torres, Natáli Valim Oliver (Frontiers in Endocrinology, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a leading cause of disability-adjusted life years (DALY). Physical exercise is an effective non-pharmacological intervention to promote glycaemic control in T2DM. However, the optimal exercise parameters for glycemic control in individuals with T2DM remain unclear. Objective: This study aimed to analyze the relationship between physical training variables – frequency, intensity, type, duration, volume, and progression – and glycemic control in individuals with T2DM. Methods: A rapid systematic literature review was conducted on PubMed and LILACS databases. The PICOT strategy was employed to define the inclusion criteria. Eligible studies had to assess the impact of exercise parameters (frequency, intensity, type, duration, volume, and progression) on glycemic control indicators, primarily glycosylated hemoglobin (HbA1c). Randomized and non-randomized clinical trials were included in the review. The methodological quality of each study was assessed using the PEDro scale (PROSPERO - CRD 42021262614). Results: Out of 1188 papers initially identified, 18 reports met the inclusion criteria and were included in the analysis. A total of 1,228 participants with T2DM (1086 in exercise groups) were included in the selected studies. Among these studies, 16 (88.9%) were RCTs and 2 (11.1%) were nRCTs. The age of participants ranged from 43.1 and 68.9 years, and the average intervention duration was 16.8 weeks. Data on adherence to the intervention, adverse events, detailed intervention protocol, and its impacts on glycaemic control, lipid profile, blood pressure, anthropometric measures, medication, body composition, and physical fitness are reported. Conclusion: The evidence supports the safety and effectiveness of physical exercises as non-pharmacological interventions for glycemic control. Aerobic, resistance and combined training interventions were associated with reductions in HbA1c and fasting glucose. The diversity of the physical exercise intervention protocols investigated in the studies included in this review is an important limitation to generalizing evidence-based practice. The call for action is mandatory to implement large-scale education programs on the prevention of diabetes and public health policies aimed to include well-planned and supervised exercise programs as an essential part of the primary prevention of type 2 diabetes.